Identifikasi Sektor Unggulan pada Perekonomian Kota Banjarmasin: Analisis Input – Output - Muhammad Ervan Ghani; M Handry Imansyah (PPJP Universitas Lambung Mangkurat, 2021)
Muhammad Ervan Ghani (2020). Identification of Leading Sektors in the Economy of Banjarmasin City: Analysis of Input Output. Advisor Prof. M. Handry Imansyah, MAM, Ph.D. This study aims to determine the leading sektors and their role in the economy in the city of BanjarmasinThis study uses analysis tools to determine the leading sektors through the calculation of Location quotient, Input - Output Analysis. By using secondary data in the form of gross regional domestic product according to employment and Expenditures on Current prices, Banjarmasin city labor, and BPS IO Table.The results showed that the leading sektors in the city of Banjarmasin were dominated by the secondary sektor, namely (1) community services and others (2) financial institutions, real estate and company services, and (3) the manufacturing industry.There are limitations in this research, namely, some data does not reach 17 sektors, so the analysis data is completely converted into 9 sektors and this research uses non-survey, so that the data used is only the result of documentation by the relevant agencies.